2013
DOI: 10.5897/ajb12.2465
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary characterization of genetic strains in clariid species, Clarias gariepinus and Heterobranchus bidorsalis using microsatellite markers

Abstract: Two Clariid species, Clarias gariepinus and Heterobranchus bidorsalis were compared at four loci using C. gariepinus microsatellite markers (Cga01, Cga02, Cga03, and Cga05). The heterozygosities observed were found to be 0.450 ± 0.050 and 0.442 ± 0.127, while 100% polymorphism was observed in both species. Overall, 95% of the samples amplified upon polymerase chain reaction (PCR) amplification and 44.3% of the total alleles observed for all the loci were heterozygote. Conformity to Hardy-Weinberg equilibrium u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
1
0
2
Order By: Relevance
“…Analysis across populations revealed a higher mean number of alleles in the cultured population (3.000 ± 0.724) than the wild (2.714 ± 0.286) with effective number of alleles at 1.705 ± 0.205 and 1.733 ± 0.230 respectively ( Table 5). The mean heterozygosity of 40.3% observed in this study is similar to the 44.3% observed by Agbebi et al [22] in a study comparing C. gariepinus and Heterobranchus bidorsalis, while the expected heterozygosity (0.361 ± 0.053) is lower than the 0.896 ± 0.111 reported by the same author. The lower expected heterozygosity may suggest reduced evolutionary potentials in these populations.…”
Section: Microsatellite Dnasupporting
confidence: 87%
See 2 more Smart Citations
“…Analysis across populations revealed a higher mean number of alleles in the cultured population (3.000 ± 0.724) than the wild (2.714 ± 0.286) with effective number of alleles at 1.705 ± 0.205 and 1.733 ± 0.230 respectively ( Table 5). The mean heterozygosity of 40.3% observed in this study is similar to the 44.3% observed by Agbebi et al [22] in a study comparing C. gariepinus and Heterobranchus bidorsalis, while the expected heterozygosity (0.361 ± 0.053) is lower than the 0.896 ± 0.111 reported by the same author. The lower expected heterozygosity may suggest reduced evolutionary potentials in these populations.…”
Section: Microsatellite Dnasupporting
confidence: 87%
“…The lower expected heterozygosity may suggest reduced evolutionary potentials in these populations. The Shannon's Information index (I=0.629 ± 0.143 and 0.591 ± 0.115) observed in this study, which are lower than previously reported Figures from similar studies [22,28] may suggest a lower or loss of genetic diversity in the studied populations.…”
Section: Microsatellite Dnacontrasting
confidence: 84%
See 1 more Smart Citation
“…Global ranking has placed Nigeria as the highest producer of catfish with total production of 1.2 million tonnes (Malomo, 2023) [11] . Catfish species have become a model fish for aquaculture due to its commercial value and favourable characteristic such as ability to withstand hash weather condition, omnivorous feeding, high reproduction, resistance to diseases and high growth rate (Agbebe et al, 2013) [1] . The two species of catfish that was investigated on are Clarias gariepinus and Heterobranchus bidorsalis and the genus Clarias can easily be differentiated from genus Heterobranchus by the presence of adipose fin in Heterobranchus and no adipose fin in Clarias (Moses & Olufeagba 2005) [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Global ranking has placed Nigeria as the highest producer of catfish with total production of 1.2 million tonnes (Malomo, 2023) [11] . Catfish species have become a model fish for aquaculture due to its commercial value and favourable characteristic such as ability to withstand hash weather condition, omnivorous feeding, high reproduction, resistance to diseases and high growth rate (Agbebe et al, 2013) [1] . The two species of catfish that was investigated on are Clarias gariepinus and Heterobranchus bidorsalis and the genus Clarias can easily be differentiated from genus Heterobranchus by the presence of adipose fin in Heterobranchus and no adipose fin in Clarias (Moses & Olufeagba 2005) [12] .…”
Section: Introductionmentioning
confidence: 99%